Vascular architecture in the bacteriogenic light organ of Euprymna tasmanica (Cephalopoda: Sepiolidae). Issue 3 (7th September 2018) - Patelunas, Anthony J.; Nishiguchi, Michele K.
Abstract: Symbiosis between southern dumpling squid, Euprymna tasmanica (Cephalopoda: Sepiolidae), and its luminescent symbiont, the bacterium Vibrio fischeri, provides an experimentally tractable system to examine interactions between the eukaryotic host and its bacterial partner. Luminescence emitted by the symbiotic bacteria provides light for the squid in a behavior termed "counter‐illumination, " which allows the squid to mask its shadow amidst downwelling moonlight. Although this association is beneficial, light generated from the bacteria requires large quantities of oxygen to maintain this energy‐consuming reaction. Therefore, we examined the vascular network within the light organ of juveniles of E. tasmanica with and without V. fischeri . Vessel type, diameter, and location of vessels were measured. Although differences between symbiotic and aposymbiotic squid demonstrated that the presence of V. fischeri does not significantly influence the extent of vascular branching at early stages of symbiotic development, these finding do provide an atlas of blood vessel distribution in the organ. Thus, these results provide a framework to understand how beneficial bacteria influence the development of a eukaryotic closed vascular network and provide insight to the evolutionary developmental dynamics that form during mutualistic interactions.